Multimedia maths - Masselis, Bieke, 1978-; De Pauw, Ivo, 1971- (Tielt : Lannoo, 2013)
This book refreshes the required maths fundamentals (systems, trigonometry and functions) to enable a successful mastering of the relevant content for pixel professionals. The initial maths basics will guide the reader through several standard topics, such as the golden section, coordinate systems, vectors and parameters. In addition to exploring the golden section, Multimedia Maths also offers surprising and reality-based insights into collision detection. Screen effects and image handling are taken to a higher level via a detailed outline of all the basic transformations. Last but not least, the authors illustrate the more advanced multimedial themes of quaternion rotation, fractal texture, Bézier curves and B-splines. The book is accompanied by a companion website. Surf to www.multimediamaths.be for online support and useful downloads.
Storme, Leo